Immunodepression by Rowson-Parr virus in mice: effect of Rowson-Parr virus and Friend leukemia complex infections on contact sensitivity in susceptible and resistant mice. - Bendinelli, M (1975)
Contact sensitivity to 2-phenyl-4-ethoxymethilene oxazolone, as a probe for cell-mediated immunity, was investigated in susceptible BALB/c and resistant C57BL/6 mice after infection with Friend leukemia complex (FLC) or with Rowson-Parr virus (RPV). In BALB/c mice, FLC depressed contact sensitivity when given before primary sensitization but had no effect on established contact sensitivity nor on the response elicited by a booster application of the sensitizer. These findings, together with the failure to alter reactivity to an aspecific inflammatory stimulus, indicate that FLC impairs the afferent limb of the response. In the same strain of mice RPV infection did not significantly depress contact sensitivity, as judged by the extent of the reaction 24 h after challenge, but slightly inhibited the early antibody-mediated phase of this reaction. In C57BL/6 mice neither viral preparation affected contact sensitivity.